Pengaruh Pengawasan terhadap Ketertiban Lalu Lintas Angkutan Umum di Kota Ambon - Dinata, Ochy Satya; Soselisa, Pieter Sammy; Ponto, Iriane Sosiawaty (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the effect of supervision on public transportation traffic order in Ambon City. Public transportation plays a crucial role in urban mobility, where traffic order is essential to ensure safety and service quality. This research employs a quantitative approach using survey data collected from public transport drivers and relevant stakeholders. Data were analyzed using statistical methods, including a partial t-test and coefficient of determination. The results indicate that supervision has a positive and statistically significant effect on traffic order (t = 3.726; p < 0.001). However, the coefficient of determination shows a very low explanatory power, with an R Square value of 0.001, indicating that supervision explains only 0.1% of the variation in traffic order. This suggests that traffic order is largely influenced by other factors beyond supervision, such as driver awareness, traffic culture, and supporting infrastructure. Despite its limited contribution, supervision remains a significant instrument in encouraging compliance and reducing traffic violations. Strengthening supervisory practices is therefore necessary to support more orderly public transportation management in Ambon City.